Studi Tingkat Pelayanan Dermaga Pelabuhan Rasau Jaya Kabupaten Kubu Raya - Aldona, Cindi Tia; Lestari, Arfena Deah; Meirany, Jasisca (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2023)
The Port of Rasau Jaya is the main access for selecting water transportation modes from Kayong Utaradistrict to Pontianak city. More efficient travel time and distance to shorten trips are the main factors inchoosing this mode of transportation. The problems that occur at this port are the lack of port facilities,the operational management of the ferry port which is not up to standard and less than optimal, and thelarge number of ships that do not have a permission to travel and often overload or carry excess cargo.This research was conducted to determine the level of dock service Port of Rasau Jaya and to optimizethe availability of docks to handle the flow of goods and passengers which tends to increase for the next5 years. The results of the research show that the Port of Rasau Jaya crossing is currently not up tostandard. From the calculation results there are several facilities that must be added, namely the lengthof the pier, the area of the terminal building, the parking area, and several other supporting facilities.This research provides a plan to develop several supporting facilities according to the needs that arevery necessary to meet the needs in the coming year and maximize the comfort of passengers at the Portof Rasan Jaya. A development plan requires high commitment from the Central Government andRegional Governments as well as related departments, so that maximum performance and servicesystems can be achieved because they are supported by adequate port support facilities.